Perancangan Website E-Commerce shop.ruanginterio.com dengan Integrasi Payment Gateway Paypal - Monoarfa, Fachrin; Setiyani, Hari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Digital transformation drives companies to adopt online-based sales systems. PT Ruang Inovasi Teknologi (RIT), which previously relied on conventional sales methods, requires an integrated e-commerce system to increase efficiency, expand market reach, and provide secure transactions. This study aims to design and develop an e-commerce website integrated with the PayPal payment gateway, including system requirements analysis, UI/UX design, and Laravel-based implementation. The method involves field studies, interviews with stakeholders, and a Minimum Viable Product (MVP) development approach. The outcome is an e-commerce platform (shop.ruanginterio.com) that supports automatic transactions and digital financial reporting, provides user-friendly checkout, and enables global market expansion.